Cellular interaction in the generation of suppressor cells and mitogen induced proliferation of intestinal mucosal leukocytes of buffalo - Kishore, Subodh; Sinha, R K; Das, S K (The Indian Journal of Animal Sciences, 2012)
Nonspecific suppressor cell and lymphoproliferative activity was induced in gut associated lymphoid tissue (GALT), viz. intestinal intraepithelial leukocytes (IELs), lamina propria leukocytes (LPL) and peripheral blood leukocytes (PBL). Depletion and reconstitution of adherent cells (macrophage/monocyte) revealed that these cells were indispensible in both the activities. Autologous as well as allogenic were equally potent. Addition of 2 mercaptoethanol (2 ME) to non-adherent cells could not substitute the macrophage requirement though 2 ME potentiated these responses in presence of adherent cells.